Millimetre Observations of Maser-Emitting Planetary Nebulae - Lucero Uscanga; José R. Rizzo; Miguel Santander-García; José F. Gómez; Luis F. Miranda; Olga Suárez; Panayotis Boumis; Mónica I. Rodríguez; Gerardo Ramos-Larios; Roldán A. Cala (Galaxies, 2022)
Observations in the millimetre bands of maser-emitting planetary nebulae (PNe) are crucial to study their circumstellar molecular gas at the beginning of the PN phase. Maser-emitting PNe are in the earliest phases of PN formation; therefore, these sources are key objects to study the molecular content during the early evolution of PNe. These circumstellar envelopes are active sites for the formation of molecules. We present preliminary results of millimetre observations with the IRAM 30 m telescope towards one PN (IRAS 17393−2727) of a sample of five maser-emitting PNe, where we detect <semantics>12</semantics>CO and <semantics>13</semantics>CO lines in both <semantics>J=1→0</semantics> and <semantics>J=2→1</semantics> transitions.